2004
DOI: 10.1080/02640410400005875
|View full text |Cite
|
Sign up to set email alerts
|

Mood responses to athletic performance in extreme environments

Abstract: Competition at elite level can require athletes to perform optimally in extreme environmental conditions. The present review focuses on mood responses in such conditions and proposes practical guidelines for those working with athletes. Different environments are considered, including altitude and extreme heat and cold.Performing in extreme heat, cold or at altitude can produce a stress response characterised by increased negative mood and relatively poor performance. Positive adaptations to extreme conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 82 publications
0
33
1
6
Order By: Relevance
“…In the study from Piehl Aulin, Svedenhag, Wide, Berglund, and Saltin (1998), 15 volunteers were exposed to 2,000 or 2,700 m above sea level. The authors found that living in a hypoxic environment for 12 hours/day and maintaining a training load in normoxic conditions did not negatively affect mood state (Lane, Terry, Stevens, Barney, & Dinsdale, 2004). This discrepancy may be explained by the fact that our study was performed at a higher altitude (equivalent to 4,500 m).…”
Section: Discussioncontrasting
confidence: 41%
“…In the study from Piehl Aulin, Svedenhag, Wide, Berglund, and Saltin (1998), 15 volunteers were exposed to 2,000 or 2,700 m above sea level. The authors found that living in a hypoxic environment for 12 hours/day and maintaining a training load in normoxic conditions did not negatively affect mood state (Lane, Terry, Stevens, Barney, & Dinsdale, 2004). This discrepancy may be explained by the fact that our study was performed at a higher altitude (equivalent to 4,500 m).…”
Section: Discussioncontrasting
confidence: 41%
“…One of the scientific papers that stands out in this regard is LeUnes' study [21], in which the author presents 57 scientific papers on this subject. Significant changes in mood and emotion are noted among athletes who take part in intensive exercise whether as a part of training or athletic competition [21][22][23][24]. A large group of scientists versed in physical therapy stress the value of physical activity when dealing with anxiety, depression or pessimistic behavior [5,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…O perfil iceberg apresentado pelos atletas durante os períodos de treinamento também sugere uma boa adaptação às cargas de treinamento pelas quais estavam passando, uma vez que, além de manterem o vigor alto, apresentaram valores mais baixos e estáveis de depressão e fadiga (Gráfico 1), características que têm sido associadas a uma boa adaptação às cargas de treinamento (LANE et al, 2004).…”
Section: Sujeitosunclassified
“…Reduções no vigor e aumentos na fadiga podem ser respostas normais a treinamentos árduos, porém essa situação ocorrer com aumento na depressão pode ser um indicativo de resposta de má adaptação às cargas de treinamento (LANE et al, 2004 …”
Section: Introductionunclassified